The self and its emotions - Kristjansson, Kristjan (Cambridge : Cambridge University Press, 2012)
This work examines the role of emotions in shaping and defining the self, proposing a stronger connection between selfhood and emotion than has been previously acknowledged. It is a crucial read for anyone interested in the intersection of self, emotions, psychology, philosophy of mind, and moral philosophy.
1. Introduction; 2. What selves are; 3. Exploring selves; 4. The emotional self; 5. Self-concept: self-esteem and self-confidence; 6. The self as moral character; 7. Self-respect; 8. Multicultural selves; 9. Self-pathologies; 10. Self-change and self-education.
Includes bibliographical references and index.
Keywords: Self; Self psychology; Self (philosophy).